2014
DOI: 10.1210/jc.2013-2667
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X Chromosome Inactivation and Female Preponderance in Autoimmune Thyroid Disease: An Association Study and Meta-Analysis

Abstract: Convincing evidence exists to support a role for skewed XCI in female subjects with AITD, which may, in part, explain the strong female preponderance observed in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 18 publications
2
51
1
2
Order By: Relevance
“…Several studies have shown that skewed XCI is associated with an increased risk of developing AITD. A meta-analysis confirmed significant skewing of XCI in women with Graves' disease (OR, 2.54; 95% CI, 1.58-4.10) and Hashimoto's disease (OR, 2.40; 95% CI, 1.10-5.26) (14). The epigenetic phenomenon of skewed XCI may, in part, explain the strong female preponderance in AITD.…”
Section: X-chromosome Inactivationmentioning
confidence: 86%
“…Several studies have shown that skewed XCI is associated with an increased risk of developing AITD. A meta-analysis confirmed significant skewing of XCI in women with Graves' disease (OR, 2.54; 95% CI, 1.58-4.10) and Hashimoto's disease (OR, 2.40; 95% CI, 1.10-5.26) (14). The epigenetic phenomenon of skewed XCI may, in part, explain the strong female preponderance in AITD.…”
Section: X-chromosome Inactivationmentioning
confidence: 86%
“…Skewed XCI has been proposed as a potential mechanism explaining the female preponderance of AITD (184). Previous studies have proven the increased frequency of skewed XCI in AITD patients (182, 184187).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…There is a balance maintained between Th1 and Th2 effects, but dysregulation can result in diseases. More recently, balance among Th17 cell subsets have come under suspicion since they control self-reactive T-cell proliferation [42][43][44][45][46] Skewed X inactivation One of the two X chromosomes in female cells may have genetic abnormalities or the X inactivation process cannot be established or maintained with the result that there is expression of abnormal X-linked proteins or abnormal protein levels due to improper X-linked dosage compensation that leads to an autoimmune response [51,53,54] Molecular mimicry Viral proteins or molecules in the diet that provoke an immune reaction could have epitopes similar to endogenous material. The immune reaction then spreads to an autoimmune reaction targeting the endogenous material.…”
Section: Hypotheses Of Autoimmune Diseasesmentioning
confidence: 99%
“…Familial skewing of X inactivation has been linked to a high rate of spontaneous abortions [49]. As far as ADs, skewed X inactivation has been reported for autoimmune thyroid disease [50,51] and systemic sclerosis [52,53], and there is a report of increased skewing in MS patients as they go from relapsing/remitting MS to progressive MS, but otherwise MS patients in general did not appear to have any significant variance from controls with regards to skewing [54]. Studies on other ADs have not yet shown skewing to be of significance although more studies are needed.…”
Section: The Bcytokine Polarization^hypothesesmentioning
confidence: 99%